Ad Networks, Consumer Tracking, and Privacy - Anna D'Annunzio; Antonio Russo (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study the relation between ad networks, consumer privacy and the online advertising market. We consider two publishers that can outsource their ad inventories to an ad network, in a market where consumers and advertisers endogenously multi-home. Differently from publishers, the ad network tracks consumers across websites, limiting wasteful repetition of ads. However, its tracking capability depends on consumer privacy-related choices (e.g., accepting third-party cookies). We show that tracking may increase or decrease the provision of ads, depending on its effect on expected advertising returns and on how audience sizes respond to ad quantities. When they decide whether to allow tracking, consumers exert a positive externality on advertisers. If tracking reduces the provision of ads, there is also a positive indirect externality on consumers. Hence, there may be too little tracking in equilibrium, even from consumers' perspective. We evaluate several privacy policies, including direct regulatory interventions and the creation of markets for the right to track consumers. Finally, we characterize the conditions such that outsourcing to the ad network expands the provision of ads compared to the case where publishers compete directly for advertisers.
Keywords: D43; D62; L82; M37; 330; advertising; ad network; internet; tracking; multi-homing; privacy